2019
DOI: 10.1108/nfs-01-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake is compromised among elderly living in agricultural settlements

Abstract: Purpose This study aims to investigate dietary intake among elderly living in agricultural settlements in comparison with a recent nutritional recommendation. Design/methodology/approach This cross-sectional study was carried out among elderly living in five agricultural settlements in Kuantan, Pahang, Malaysia. Participants were interviewed on socio-demographic information such as age, gender, marital status, smoking status, household income, education level and living status. Data on individual dietary int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This study shows a significant difference between genders in dietary nutrient intakes regarding carbohydrates, calcium, iron, phosphorus, selenium, zinc, vitamin C, and vitamin K. The male OA had a significantly higher carbohydrate intake than the female OA but the percentage of carbohydrate deficiency in males was higher (56.5%) than in females (52.5%). The patterns are similar to other studies conducted among the OA in Malaysia and China [ 9 , 12 , 13 ]. This study also found that the female consumed a significantly higher amount of calcium compared to the male OA and calcium deficiency was more prevalent among females (92.1%) than males (86.4%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study shows a significant difference between genders in dietary nutrient intakes regarding carbohydrates, calcium, iron, phosphorus, selenium, zinc, vitamin C, and vitamin K. The male OA had a significantly higher carbohydrate intake than the female OA but the percentage of carbohydrate deficiency in males was higher (56.5%) than in females (52.5%). The patterns are similar to other studies conducted among the OA in Malaysia and China [ 9 , 12 , 13 ]. This study also found that the female consumed a significantly higher amount of calcium compared to the male OA and calcium deficiency was more prevalent among females (92.1%) than males (86.4%).…”
Section: Discussionsupporting
confidence: 90%
“…A previous study done in Malaysia has reported that the OA was nutritionally deficient for, in particular, vitamin E, vitamin B 1 , vitamin B 3 , vitamin B 9 , calcium, and zinc [12]. While another Malaysian study focusing on the OA living in agricultural settlements has found that most of this population does not meet the recommended nutrient intake (RNI) for calcium, vitamin D, and vitamin B 2 [13]. Several studies have reported that gender, residency area (urban and rural), and socioeconomic status (SES) are associated with nutrition intakes among the OA [9,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite lower global prevalence of malnutrition among elderly in the community compared to other settings, a higher prevalence was recorded in Malaysia. A range from 25.7% to 64.0% of Malaysian elderly living in the community have been classified as at-risk and malnourished (11)(12)(13)(14). This shows a call for action to tackle malnutrition issue, especially among Malaysian community living elderly, which should be done systematically, as no published intervention studies were identified in this setting.…”
Section: Introductionmentioning
confidence: 99%